Rancangan Katalog Kartu Untuk Temu-Balik Surat Masuk dan Surat Keluar Tata Usaha Kantor Perpustakaan Arsip dan Dokumentasi Kabupaten Pesisir Selatan - Nelsya, Nadia Lutfia; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purpose of this study is to describe the design of the card catalog in letter retrieval system at administrative Office of Library Archives and Documentation of Pesisir Selatan District. Data were collected through observation and in a descriptive research. Based on data analysis, stage of making a card catalog is (1) determining the physica, storange used letters; (2) determining the size of the card catalog designed; (3) determining specifying the information to be entered to the card catalog; (4) determining the storange and preparation of catalog cards; (5) determining the storange system used to store the card catalog. Results obtained from these data is the card catalog for incoming and outgoing letter are (1) the physical from letters storange system was used between chronological and alphabetical combinations; (2) catalog size is 7.5 x 12.5 cm with a thickness of 0.025 cm; (3) the contents of the catalog are the placement of numbers, letters home, letters purposes, subject date entry/exit date, number of letters, attachments; (4) storage cabinets catalog using for card catalogs; (5) theÂ letters storage system based on the alphabet name of the sender, recipient or subject; (6) focus on the search procedure for finding a storage code letter that guides the user to the resources letters needed. Keywords: catalog; letter; retrieval Â